2019
DOI: 10.18632/oncotarget.26889
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput screen of pharmacologically active compounds for inhibitors of UHRF1 reveals epigenetic activity of anthracycline derivative chemotherapeutic drugs

Abstract: DNA methylation can mediate epigenetic silencing of tumor suppressor and cancer protective genes. The protein ubiquitin-like containing PHD and ring finger domains 1 (UHRF1) is an essential component in cells for DNA methylation maintenance. The SET- and RING-associated (SRA) domain of UHRF1 can bind hemimethylated DNA, and mediate recruitment of DNA methyltransferases to copy the methylation pattern to the newly synthesized daughter strand. Loss of UHRF1 function can lead to demethylation and re-expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…In line with this hypothesis, UM63 was found to decrease the global DNA methylation level by more than 40 % in HeLa cells. A similar effect was observed when UHRF1 was knocked‐down with shRNAs in HeLa cells, or when the binding of the SRA domain to HM DNA was prevented by anthracycline derivatives, highlighting the key role of UHRF1 in the maintenance of the DNA methylation level. These findings strongly suggest that UM63 can target UHRF1 in the cellular context.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In line with this hypothesis, UM63 was found to decrease the global DNA methylation level by more than 40 % in HeLa cells. A similar effect was observed when UHRF1 was knocked‐down with shRNAs in HeLa cells, or when the binding of the SRA domain to HM DNA was prevented by anthracycline derivatives, highlighting the key role of UHRF1 in the maintenance of the DNA methylation level. These findings strongly suggest that UM63 can target UHRF1 in the cellular context.…”
Section: Discussionmentioning
confidence: 60%
“…Finally, mitoxantrone, a topoisomerase II inhibitor of the anthracycline family, has also been reported to alter the binding of the SRA domain to HM DNA and induce hypomethylation with subsequent re‐expression of tumor suppressor genes (TSGs) . Very recently, a time‐resolved fluorescence resonance energy transfer (TR‐FRET) assay based on the binding of SRA to HM DNA was used to screen the library of pharmacologically active compounds (LOPAC) . This screening confirmed that mitoxantrone as well as four other topoisomerase II inhibitors of the anthracycline family can inhibit the SRA binding to HM DNA and induce dose‐responsive global DNA demethylation.…”
Section: Introductionmentioning
confidence: 91%
“…Since UHRF1 is overexpressed in a wide variety of solid tumours and it is not required in non-replicating cells, its downregulation could be used to overcome the resistance to DNA damaging agents by impairing DNA repair mechanisms. While several approaches have been tested to inhibit the different domains of UHRF1 ( 149 , 150 ), a recent work focused specifically on targeting UHRF1 functions in DNA damage repair ( 151 ). Here it is shown that in prostate cancer cells, the combined treatment with HDAC and PARP inhibitors (SAHA and veliparib) disrupts the interaction between UHRF1 and BRCA1 and decreases UHRF1 and BRCA1 levels, resulting in inhibition of the HR pathway and cell death ( 151 ).…”
Section: Uhrf1 In Dna Damage Response As a Potential Therapeutic Targetmentioning
confidence: 99%
“…This suggests that UHRF1 expression is essential for faithfully maintaining DNA methylation and for preserving the chromatin state within heterochromatic regions of the genome, which is consistent with its function as a link between repressive histone modifications and the DNA methylation machinery. Ultimate confirmation of the role of UHRF1 in leukemic patients will require mouse knockdown/transplantation and/or design of UHRF1 -specific inhibitors for preclinical or clinical investigation, in addition to nonspecific agents which act on this target and are under investigation in prostate and colon cancer 57 . This however is beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%